Voting in online surveys on open government policies in Moldova and Ukraine - Dmytro Khutkyy; Olga Matveieva; Diana Mirza-Grisco (Internet Policy Review, 2023)
The socio-political impact of voting in online surveys on open government is understudied. This inquiry aims to identify the socio-political impact of voting in online surveys on voters, civil society organisations, government authorities and open government overall in Moldova and Ukraine in 2016 and in 2018. This article applies mixed methods of data collection and analysis: analysis of applied reports, policy analysis of documentation, manual qualitative content analysis of social media posts and of digital voting tools and semi-structured expert interviews of stakeholders. We found that the voting in online surveys for Open Government Partnership commitments influences open government, although more profoundly in Ukraine than in Moldova. Probably, this is due to more intensive and innovative multistakeholder efforts to implement civic education, transparency and accountability in Ukraine. The voting in online surveys occurred at dissimilar stages of policy-making: in Moldova - at the agenda-setting stage, while in Ukraine - at the policy-drafting and decision-making stages. In both countries, the impact of voting in online surveys was more manifest on collaboration between the public and the authorities than on civil society and the least on the authorities. Overall, a formally non-binding voting for policy priorities became an informally binding exercise.
Keywords: 300; Open government; Online surveys; Ukraine; Moldova; Voting behaviour